The Relationship of Knowledge of Hands Washing with The Event of Diarrhea - Bolon, Christina Magdalena T. (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Diarrhea is a condition of abnormal or unusual stool output, characterized by an increase in volume, dilution and frequency more than 3 times a day. using a questionnaire as an instrument, with a descriptive correlative research design that uses a cross-sectional approach. The sampling technique in this study is accidental sampling with a sample of 25 students at Imelda Private Elementary School Medan. Data analysis uses the chi-square test. good and never experienced diarrhea as many as 2 people and had experienced diarrhea as many as 6 people. Respondents who have good knowledge of handwashing and have never experienced diarrhea are 5 people and have experienced diarrhea as many as 4 people. Respondents who have good handwashing knowledge and have never experienced diarrhea are 7 people and have experienced diarrhea as many as 1 person.